Spriritual Konsumsi dalam Ekonomi Islam: Pendekatan Filsafat dan Al Qur’an: Spriritual Konsumsi dalam Ekonomi Islam: Pendekatan Filsafat dan Al Qur’an - Moh Arifin arifin (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2021)
The existence of intense competition requires a bank to compete in controlling the market and even want to be in the most influential position in the competitive market. A bank needs to conduct a study in marketing strategy because it aims to test and assess the extent to which the marketing of the products produced can support the development of a planned business or business. The marketing strategy in the economic sector in Indonesia is developing quite rapidly, one of the most important things in the economic sector is marketing. Wherever a company is established, it must have a strategy to excel in competing in developing and advancing its company, such as in the financial sector.The marketing strategy in the economic sector in Indonesia is developing quite rapidly, one of the most important things in the economic sector is marketing. Wherever a company is established, it must have a strategy to excel in competing in developing and advancing its company, such as in the financial sector. PT BPRS Madinah Lamongan is one of the Islamic people's finance banks in the city of Lamongan. The purpose of this study was to determine the marketing strategy of financing products in increasing competitive advantage according to the Islamic economic perspective at PT. BPRS Madinah Lamongan, this type of research is qualitative research. The data analysis used in this research is the SWOT analysis method.The results of this study indicate that the product marketing strategy applied by PT. BPRS Madinah in increasing competitive advantage according to the perspective of Islamic economics, which is implemented using a marketing mix analysis consisting of 4P product (product), price (price), promotion (promotion), place (place).